(untitled) (Bodhi Path, 2024)
Tibetan Buddhism, also known as Vajrayana Buddhism, emerged in the Himalayan region, primarily in Tibet, and is notable for its unique blend of Mahayana teachings, tantric practices, meditation, and ritual, under the guidance of spiritual teachers known as Lamas. According to tradition, Buddhism first appeared in Tibet during the fourth century CE, under King Lha-tho-ri-gnyan-bstan, when sacred texts reportedly fell from the sky onto the king’s palace. These texts remained undeciphered until King Songsten Gampo’s reign, when he established Buddhism as the state religion by marrying Buddhist princesses from Nepal and China. Songsten Gampo’s minister, Thonmi Sambhota, developed a Tibetan script and grammar, facilitating the translation of key Buddhist texts from Sanskrit to Tibetan. Indian scholars such as Padmasambhava and Shantarakshita significantly contributed to this early transmission. This paper examines the origins of the Tibetan script and the pivotal role of textual translations in the dissemination of Tibetan Buddhism throughout the Himalayas. It explores the development of Tibetan writing and emphasizes the critical process of translating Buddhist texts from Sanskrit to Tibetan, which was instrumental in preserving and establishing Buddhist teachings in Tibet.